The impact of granulocyte colony-stimulating factor (G-CSF) on thin endometrium of an animal model with rats. (4th May 2021) - Işık, G.; Oktem, M.; Guler, I.; Oktem, E.; Ozogul, C.; Saribas, S.; Erdem, A.; Erdem, M.
Abstract: Purpose: To evaluate whether G-CSF improves the endometrial thickness of thin endometrium by influencing proliferative, angiogenic and apoptotic factors, an experimental rat model was conducted using 24 female adult rats with either thin or healthy endometrium that each was further divided into G-CSF or saline injection groups with six rats. Materials and methods: After forming of the thin endometrium by uterine injection of 0.2 ml 96% ethyl alcohol to the rats, five days of subcutaneous injections of 40 μg/kg G-CSF or saline were given. Endometrial thickness, immunohistochemically expression of vascular endothelial growth factor receptor-2 (VEGF-R2), proliferative cell nuclear antigen (PCNA) and fibronectin apoptosis with TUNEL method were compared in specimens among four groups of post-model rats. Results: Endometrial thickness was significantly improved in thin but not in normal endometrium group with GCSF when compared to saline injection. Stromal and glandular epithelial expression of PCNA and pericapillary VEGF-R2 was significantly increased, and apoptosis was significantly decreased with G-CSF. Although fibronectin was also increased with G-CSF in the thin endometrium, the difference was non-significant. In further, G-CSF decreased apoptotic cells and increased expression of PCNA when compared to saline injection in normal endometrium. Conclusions: G-CSF improves endometrial thickness, proliferation, angiogenesis and DNA fragmentation in thin endometrium.